EFFORTS TO IMPROVE LEARNING MOTIVATION OF STUDENT WITH CONTENT MASTERY IN SMP NEGERI 1 METRO - Pranoto, Hadi (Universitas Muhammadiyah Metro, 2013)
Abstract: The study design using action research applied in guidance and counseling services (follow-services research). Subjects in this study, researchers took VII.4 grade students of SMP Negeri 1 Metro Odd Semester Lesson Tabun 2012/2013. Of the 24 students, there are 10 students who experience a lack of motivation to learn to 41.66%. The method used in collecting data by observation and field notes. Analysis of the data used is the analysis of qualitative and quantitative data. Validity test is done through assessment experts /specialists ie counseling teachers SMP Negeri 1 Metro, other friends peer discussions that instrument with other friends FKIP students with courses in counseling. The results of this study, it can be concluded that the results obtained through the implementation of the procurement of content services in increasing the motivation of learners class VII.4 SMP Negeri 1 Metro Tabun Odd Semester Lesson 20 12/20 13 is visible from the change in behavior and ability of learners in learners become more willing to meet the needs of achievement, students can understand or have confidence in learning, learners have the ability to overcome failure in learning, and learners have a good competitiveness in the service learning. Through mastery of content supplied by BK teacher can increase the motivation of learners class VII.4 SMP Negeri 1 Metro Odd Semester Academic Year 201212013. There is increased the motivation of learners in the first cycle seen from the average percentage that is equal to 27.5% and in the second cycle of 75 %, resulting in an increase of 47.5%. Response and activity VIl.4 grade students of SMP Negeri 1 Metro Odd Semester Lesson Tabun 2012/2013 on the service in the content mastery enhance learning motivation is very positive, it is shown by the participation of learners in the service following the mastery of content, learner motivation and enthusiasm in participating services as well as content mastery learners were active in service activities mastery of the content.Keyword: Motivation, Content Mastery Service.